Pengungsi dalam Kerangka Kebijakan Keimigrasian Indonesia Kini dan yang Akan Datang - Havid, Ajat Sudrajat (UI Scholars Hub, 2004)
Being a transtitory destination, Indonesia has been drawn into the problem of refugees. Since 1979, when Vietnam was tormented by war, up to the recent times, when tumoil and instability erupted in the Middle East and South East, thousands refugees have fled their countries and Indonesia has received the clausative predicaments of their being illegally stranded in Indonesian territory. Indonesia is not a paty to the 1951 The UN Convention relating to the Status of Refugees and its Protocol of 1967. That being the case, Indonesia is not the legal obligations of the convention. However, Indonesia has established a strong legal basis concerning the human rights (including the aspect of asylum and refugees). Decision of the People’s Consultative Assembly TAP MOR XVII/MPR/1997 on Human Rights, Law No. 37/1999 on Foreign Relations and the Law No. 39/1999 on Human Rights. Indonesia’s handling of refugees problems is a testimary of Indonesia’s determination in upholding human rights. Therefore, an administrative circular note issued set by Director General of Immigration on 30 September 2002 on the Directions to Proceure of Handling the Self-claimed Asylum Seekers and Refugees, Indonesian immigration authority allows UNHCR and IOM to give temporary protection and facilitation by UNHCR protecting officer. The two international bodies managed to resolve refugee problems, namely managing voluntary return or resettlement to the third countries. Meanwhile, operational regulations to execute refugees and asylum seekers handling in Indonesia as prescribe in the above mentioned laws are still pending. In the future, alternatively, immigration law shall adopt the human rights values without abandoning the immigration selective policy.